2021
DOI: 10.3390/ijerph18189777
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Factors Influencing Dietary Patterns of University Professors

Abstract: The objectives of this study are to identify eating patterns of university professors and to assess the relationships among sociodemographic factors in relation to lifestyle and physical activity. It is a cross-sectional, descriptive-correlational, and observational study with a representative sample of 127 educators, which covers almost the total population of university professors belonging to one of the campuses of the University of Granada (Spain). Two eating patterns were identified a posteriori through e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…Consistent with the present findings, results from two comparable Austrian surveys on schoolteachers showed that the prevalence of overweight/obesity was remarkably higher in males (40.6 and 46.5%) than in females (14.7 and 29.2%) (55, 65). According to a Spanish study, a greater proportion of male and female university professors were found to be overweight or obese (64.5% of males and 36.9% of females) (43). While the prevalence of overweight/obesity is higher among the general population of Austrian adults compared to academics, the sex difference between males and females has been reported to be much smaller (66).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with the present findings, results from two comparable Austrian surveys on schoolteachers showed that the prevalence of overweight/obesity was remarkably higher in males (40.6 and 46.5%) than in females (14.7 and 29.2%) (55, 65). According to a Spanish study, a greater proportion of male and female university professors were found to be overweight or obese (64.5% of males and 36.9% of females) (43). While the prevalence of overweight/obesity is higher among the general population of Austrian adults compared to academics, the sex difference between males and females has been reported to be much smaller (66).…”
Section: Discussionmentioning
confidence: 99%
“…University professors and lecturers are prestigious role models and multipliers with great responsibility and power who are especially impactful in developing society's sociocultural structure and fostering healthier behaviors within academic and professional environments (41,42). University academics are at risk and face challenges in maintaining optimal health behavior, mostly due to time constraints and demanding schedules (43). In particular, tertiary faculty members have fundamentally stressful and demanding professions as they experience various stressors, including limited leisure time, inadequate rest, insufficient sleep (43,44), which may weaken other health behaviors such as PA and dietary patterns (43,45).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying and describing the DP and its related factors can lead to effective measures to prevent the consequences of unhealthy DPs [ 6 ]. Eating restriction (ER) is one of the factors that influence DP [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is a decreasing tendency toward fruit consumption, both in terms of raw fruits and juices [3,4]. This tendency has also been observed among the youngest consumers (children) [5,6], youth and young adults (students) [7][8][9], and adults (professionally active people) [10,11]. With regard to children, it has been found that the younger they are, the lower their frequency of consuming processed fruit [6].…”
Section: Introductionmentioning
confidence: 99%